Development of a buoyancy control device for autonomous underwater vehicle - Syafie, Lia Safiyah; Zainal Abidin, Zulkifli; Alang Rashid, Nahrul Khair (Institute of Electrical and Electronics Engineers Inc., 2016)
The development of Autonomous Underwater Vehicle (AUV) or known as unmanned underwater vehicle increase exponentially in these recent years. This is due to the increase of demand in many applications such as prospecting on the seafloor and other underwater tasks without human interference and supervision. This vehicle can be used to perform underwater missions such as surveys, monitoring, image capturing and other applications. In achieving given tasks, AUVs must capable to control its depth level. Thus, a buoyancy control device (BCD) is developed to assist AUV in controlling its depth level. This paper is focusing in developing a volume based BCD. A pair of rubber bellow is simulated as the main hardware to vary the volume of BCD while keeping a constant mass. To execute this method, an input (depth level) is required from user through a Graphical User Interface (GUI) provided. Water level transducer is used to measure the current level of the BCD and compare with the user input. By this comparison, BCD will compensate with water density, in order to achieve positive, negative or neutral buoyancy based on the desired input value. This system is a close loop system with a Proportional Integral Derivatives (PID) controller integrated for the controller. PID controller will continuously calculates the error value as the difference between the desired (user input) and the actual value measured. PID controller is designed to reduce the oscillation occurred in the system during autonomous adjustments with a suitable gain values. This paper proved that by controlling the volume of the bladder, depth level of BCD also can be controlled accordingly with 47% maximum and 2% minimum error occurred.